Construcción de habilidades psicosociales en escenarios escolares una alternativa frente al riesgo de xenofobia, dentro del marco del proyecto: pedagogía y protección de niños, niñas y adolescentes migrantes venezolanos. Convenio ACNUR-sed-Col. - Rodríguez Pedraza, Pablo Enrique (Universidad Antonio Nariño, 2021)
Migration is a phenomenon that has accompanied humanity throughout its existence, being a way out of social, political and economic problems, a hopeful way to solve extreme situations of poverty and famine. Currently, Colombia suffers one of the largest migratory phenomena of modernity, receiving thousands of Venezuelans daily. Based on the emerging psychosocial model, participatory action research was used as the main work methodology, being this an active tool in the evaluation and feedback of this qualitative research process. Five (5) public schools in the Colombian capital, one hundred seventy (170) teachers, more than two hundred and fifty (250) children and adolescents and one hundred (100) parents were part of this process. With the execution of this proposal, the leadership processes of Venezuelan youth were strengthened, inter-institutional connections to attend to the needs of Venezuelan families, train teaching staff in adaptability and adequate pedagogy to support the migrant student. As a conclusion, the need to generate central and district public policies according to the needs of migrants is visible, pedagogical adaptability to school processes of migrant students, creation of sustainable and sustainable school projects. Schools and colleges have become the place with the greatest reception of migrant children and adolescents due to their free accessibility and compliance with the right to education. On a social level, Colombia is one of the countries with the greatest problems, in terms of unemployment and lack of opportunities. Furthermore, for many reasons, the gaze of public opinion on Venezuelans is unfavorable, since they are seen as invaders up to the point of compare them to a disease.